2019
DOI: 10.2147/dmso.s206069
|View full text |Cite
|
Sign up to set email alerts
|

<p>Risk analysis of systemic levels of estrogen and adipokines as well as estrogen receptors from PBMCs in childbearing and perimenopausal women with obesity</p>

Abstract: Purpose We aimed to evaluate the clinical value of systemic levels of estrogen and adipokines as well as estrogen receptors from peripheral blood mononuclear cells (PBMCs) in childbearing and perimenopausal women with obesity. Subjects and methods We observed 292 women, including 160 perimenopausal women (80 with obesity and 80 without obesity) and 132 women of childbearing age (67 with obesity and 65 without obesity). Body parameters, such as body mass index and waist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Fan et al, in 2019, observed that decreased levels of physical activity and low musculoskeletal activation in postmenopausal women, increased the cardiovascular risk associated with the reduction of leptin and adiponectin plasma concentrations, increased insulin resistance and body weight gain by the extent of adipose tissue. 24 These findings are associated with those found in this study, where obese women spend less average energy on physical activity compared to women with normal BMI.…”
Section: Discussionsupporting
confidence: 82%
“…Fan et al, in 2019, observed that decreased levels of physical activity and low musculoskeletal activation in postmenopausal women, increased the cardiovascular risk associated with the reduction of leptin and adiponectin plasma concentrations, increased insulin resistance and body weight gain by the extent of adipose tissue. 24 These findings are associated with those found in this study, where obese women spend less average energy on physical activity compared to women with normal BMI.…”
Section: Discussionsupporting
confidence: 82%
“…These (5 ml) were collected and centrifuged for 15 min at 3,500 rpm and then were preserved at −80°C for subsequent experiments. Because the estrogen level may be one of the factors affecting the results, the serum estrogen levels were measured using a standard enzyme-linked immunosorbent assay, which was as described in our previous study (6).…”
Section: Clinical Indices and Serum Sample Collectionmentioning
confidence: 99%
“…The pathophysiological state of PO is quite complicated. It is influenced by many pathogenic factors, of which estrogen deficiency plays a key role (6). The complicated interactions among these factors sometimes make the situation intractable.…”
Section: Introductionmentioning
confidence: 99%
“…One of obesity's main links to the problem of cancer is that it usually involves an increase in visceral fat, which leads to significantly increased insulin hormonal activity. This onset of visceral fat can be augmented by the onset of menopause wherein the lowered levels of circulating estrogen may lead to a loss of subcutaneous fat and an increase in visceral fat, for estrogen has been linked to the accumulation of subcutaneous fat (7). This change in fat distribution implicates a major role for estrogen in the development of post-menopausal obesity, making it a candidate for examination in the discussion of the development of EC.…”
Section: Ivyspringmentioning
confidence: 99%